The relevance of theobromine for the beneficial effects of cocoa consumption - Martínez-Pinilla, Eva; Oñatibia-Astibia, Ainhoa; Franco, Rafael (Frontiers in Pharmacology, 2015)
Cocoa consumption began in America and in the mid 16th Century it quickly spread to Europe. Beyond being considered a pleasant habit due to its rich sweet lingering taste, chocolate was considered a good nutrient and even a medicine. Traditionally, health benefits of cocoa have been related with the high content of antioxidants of Theobroma cocoa beans. However, the direct psychoactive effect due to methylxanthines in cocoa is notable. Theobromine and caffeine in the proportions found in cocoa are responsible for the liking of the food/beverage. These compounds influence in a positive way our moods and our state of alertness. Theobromine, which is found in higher amounts than caffeine, seems to be behind several effects attributed to cocoa intake. The main mechanisms of action are inhibition of phosphodiesterases and blockade of adenosine receptors. Further mechanisms are being explored to better understand the health benefits associated to theobromine consumption. Unlike what happens in other mammals –pets included-, theobromine is safe for humans and has fewer unwanted effects than caffeine. Therefore, theobromine deserves attention as one of the most attractive molecules in cocoa.